Evaluating the Impact of Various Macroeconomic Indicators on the Fiscal Freedom Index in the European Union - Nicoleta-Iulia POPESCU-BODEA; Mihaela-Ionela STANCIUC (SOCOLIUC) (Communications of International Proceedings, 2022)
The econometric modelling of the Fiscal Freedom Index through different macreconomic indicators is a scientificendevour that has a significant practical use, considering the fact that it could help fundament the decisional process of fiscal and economical policymakers, in order to help improve the overall collection levels of revenues to the state budgets and ensure a sustainable development for the business environment. The purpose of this research is to evaluate and quantify the impact of a series of macroeconomic indicators on the Fiscal Freedom Index, using regressional analysis, on a panel of 27 EU member states, for the period 2016 – 2020. The main results of the research showed that 76.80%, of the change in the Fiscal Freedom Index can be accounted for by the changes in the independent variables used in the econometrical model (Total Tax Revenue as a Percentage of GDP, Regulatory Quality Index, Economic Growth, GDP per Capita, Control of Corruption Index, Effective Average Tax Rates and Unemployment by Sex, Age and Educational Attainment). According to the processed data, the most statistically significant variables in the model are Effective Average Tax Rates, GDP per capita and Tax revenue as a percentage of GDP. This research contributes significantly to the field of knowledge as it can provide useful conclusions and results for the elaboration and implementation of sustainable macroeonomic and fiscal policies.
Keywords: European Union; Evaluation; Fiscal Freedom Index; Regression Analysis